2002
DOI: 10.1021/ma020451z
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation Lifetime Spectroscopy (PALS) for Interdiffusion Studies in Disperse Blends of Compatible Polymers:  A Quantitative Analysis

Abstract: Positron annihilation lifetime spectroscopy (PALS) and differential scanning calorimetry (DSC) were used to study the interdiffusion in a particle-matrix system consisting of the miscible polymers poly(vinyl chloride) (particles) and poly(n-butyl methacrylate) (matrix, 30:70 and 50:50 w/w). Starting from the demixed state of the blends, the transition to the mixed state during annealing at 110 °C was investigated. We deliver further evidence that PALS parameters such as the orthopositronium intensity I 3 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 39 publications
4
45
0
Order By: Relevance
“…We have shown that the o-Ps intensity I 3 , which mirrors the Ps yield, depends on whether Ps inhibitors are distributed throughout a material homogeneously or heterogeneously. This effect can be used to study the interdiffusion in an originally demixed blend of two miscible polymers [Dlubek et al, 2002c] or the opposite process, the demixing of originally mixed polymers [Günther-Schade et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the o-Ps intensity I 3 , which mirrors the Ps yield, depends on whether Ps inhibitors are distributed throughout a material homogeneously or heterogeneously. This effect can be used to study the interdiffusion in an originally demixed blend of two miscible polymers [Dlubek et al, 2002c] or the opposite process, the demixing of originally mixed polymers [Günther-Schade et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…The o-Ps intensity I 3 , which mirrors the Ps yield, depends on whether inhibitors for the Ps formation are homogeneously or heterogeneously distributed in a material (163)(164)(165). This effect can be used to study the interdiffusion in an originally demixed blend of two miscible polymers.…”
Section: Positron Annihilation As a Chemical Probe For Polymersmentioning
confidence: 99%
“…We find several studies reported on the interfacial properties in terms of interdiffusion at the interface, [22][23][24][25][26] interfacial tension, [27][28][29][30] and interface width, 21,[31][32][33][34] and so forth in polymer blends. The magnitude and behavior of interface width with varying molecular weight, temperature, and film thickness have also been studied using the small angle neutron scattering, neutron reflectometry, 27,28,[33][34][35] small angle X-ray scattering, differential scanning calorimetry (DSC), 26 transmission electron microscopy, 30 and so forth with varying success.…”
Section: Introductionmentioning
confidence: 92%